Activity determination of 137Cs in NPL’s ampoule using a point source - Supian Bin Samat (Universiti Kebangsaan Malaysia, 1997)
The activity of two liquid mixed radionuclide sources in NPL'S standard glass ampoules were determined by gamma-ray spectrometry measurement using a standard point source placed at 38.5 cm axially above the detector. A radio nuclide 137Cs was chosen, Results obtained were within 3% agreement with the calculated value. The same degree of deviation was obtained when the NPL standard source of equal geometry, chemical composition and density was used.